Profil kolaborasi guru bimbingan dan konseling dengan guru mata pelajaran dalam mengatasi kesulitan belajar di kelas XI IPS SMA Negeri 13 Padang - Septya Suarja; Ahmad Dayat (Indonesian Journal of Counseling and Development, 2022)
This research is motivated by the lack of collaboration between Guidance and Counseling Teachers and Subject Teachers in overcoming learning difficulties experienced by students. This study aims to determine the form of collaboration carried out by the Guidance and Counseling teacher with subject teachers in diagnosing learning difficulties in the form of 1) identifying students who have learning difficulties, 2) determining the location of students' learning difficulties, and 3) determining the factors causing the occurrence. Learning difficulties in students. This research uses a descriptive qualitative method. The key informants of this study were two counselling teachers and two subject teachers; additional informants were two teachers who taught in class XI IPS at SMAN 13 Padang. This study uses interviews as a technique for collecting data. Data analysis consists of three stages: data reduction for grouping data relevant to the research objectives and focus, data presentation, and conclusion. The study results revealed: 1) Collaboration between counselling teachers and subject teachers in identifying students with learning difficulties, namely providing information and discussing the data collected to determine students who have learning difficulties. 2) Collaboration between guidance and counselling teachers and subject teachers in determining the location of student learning difficulties, namely exchanging information and communicating informally in determining how to locate student learning difficulties. 3) Collaboration between guidance and counselling teachers and subject teachers in determining the factors causing student learning difficulties, namely conducting discussions, counselling, and discussing. The results of this study are recommended for counselling teachers to collaborate with other parties such as subject teachers, school principals, parents, and other parties to overcome students' learning difficulties